Ten Years of Lithuanian Reforms: Solutions, Nonsolutions, Problems, Prospects - Samanis, Valdas (Ekonomika, 2000)
The paper takes a comparative look at the decade of Lithuanian reforms from a global strategic perspective. Some key macro- and micro-level economic reforms in Lithuania arc briefly presented and assessed against the background of such reforms in other postcommunist countries. The paper argues that the state role is one of the most important problems still unreslved in Lithuania and other transition economics. This problem should be remedied by the second generation reforms to be carreid out in the context of the European and global integration with special reference to the requirements of the digital era: Thus, the paper outlines some guidelines for the development of the new state role in Lithuania and proposes a number of specific recommendations. especially in the areas of interaction among state, society, and economy. More work along these lines is planned for the next stage of this research.